2016
DOI: 10.1212/wnl.0000000000002587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waivers of consent on recruitment in acute stroke trials

Abstract: There is urgent need for clinical trials of novel interventions to reduce the burden of acute ischemic stroke. A key impediment to such trials is slow recruitment. Since obtaining written informed consent in the setting of acute stroke is especially challenging, some experts have endorsed relaxing the requirement for informed consent by permitting verbal consent or waivers to facilitate recruitment. This systematic review of 36 randomized controlled trials of acute interventions for ischemic stroke assesses wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 62 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…A systematic review and metaanalysis of 114 large scale (> 300 participants) acute (within 1 month after stroke) pharmacological stroke trials published between 1990 and 2004 reported a mean recruitment rate of 0.79 participants per site per month [13]. An update of this study revealed a median recruitment rate of 0.41 participants per site per month for trials published between 2010 and 2014 [24]. Despite notable difficulties recruiting stroke survivors, and limited improvement over the past 27 years [13,14], little research has focused on recruitment of stroke survivors to rehabilitation RCTs.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A systematic review and metaanalysis of 114 large scale (> 300 participants) acute (within 1 month after stroke) pharmacological stroke trials published between 1990 and 2004 reported a mean recruitment rate of 0.79 participants per site per month [13]. An update of this study revealed a median recruitment rate of 0.41 participants per site per month for trials published between 2010 and 2014 [24]. Despite notable difficulties recruiting stroke survivors, and limited improvement over the past 27 years [13,14], little research has focused on recruitment of stroke survivors to rehabilitation RCTs.…”
Section: Introductionmentioning
confidence: 85%
“…Recruitment of stroke survivors to clinical trials is challenging [13,14,24]. In the UK more than 100,000 people experience a stroke each year [25,26] and there are currently 1.2 million people living with strokerelated impairments [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…12 The recruitment efficiency of that trial was 10.5 participants/site/month, and the recruitment rate was 294.4 participants/month—both far higher than the trials in this review and indeed far higher than other recent field-based trials with opt-in enrollment. 8 We specifically excluded field-based trials from this review to enable proper comparison of newer trials to those in the Elkins dataset, which included only hospital-based interventions. But field-based interventions designed to improve the speed with which stroke therapy is delivered may also enhance the recruitment of trials as more participants are reached before the time window for inclusion closes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Opt-out strategies raise challenging ethical questions, which merit further examination, but they have gained increasing acceptance by institutional review boards (IRBs) and the Food and Drug Administration. 8 Whether such opt-out strategies become more prevalent in acute stroke trials remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation